Myxozoan hidden diversity: the case of Myxobolus pseudodispar Gorbunova, 1936 - Lisnerova, Martina; Blabolil, Petr; Holzer, Astrid; Jurajda, Pavel; Fiala, Ivan (Folia parasitologica, 2020)
Myxobolus pseudodispar Gorbunova, 1936 (Myxozoa) was originally described as a parasite of common roach, Rutilus rutilus (Linnaeus), with developing stages in muscles and spores disseminated in macrophage centres of different organs and tissues. Later, this parasite was described from several other cyprinids, but with relatively large intraspecific differences based on SSU rDNA gene sequences. Within our long-term study on myxozoan biodiversity, we performed a broad microscopic and molecular screening of various freshwater fish species (over 450 specimens, 36 species) from different localities. We investigated the cryptic species status of M. pseudodispar. Our analysis revealed four new unique SSU rDNA sequences of M. pseudodispar as well as an infection in new fish host species. Myxobolus pseudodispar sequence analysis showed clear phylogenetic grouping according to fish host criterion forming 13 well-recognised clades. Using 1% SSU rDNA-based genetic distance criterion, at least ten new species of Myxobolus Bütschli, 1882 may be recognised in the group of M. pseudodispar sequences. Our analysis showed the paraphyletic character of M. pseudodispar sequences and the statistical tests rejected hypothetical tree topology with the monophyletic status of the M. pseudodispar group. Myxobolus pseudodispar represents a species complex and it is a typical example of myxozoan hidden diversity phenomenon confirming myxozoans as an evolutionary very successful group of parasites with a great ability to adapt to a new hosts with subsequent speciation events.
Keywords: Animals; biodiverzita; ribozomální DNA; biologická evoluce; DNA, Ribosomal; Myxobolus; PCR screening; Host-Parasite Interactions; Parasitic Diseases, Animal; interakce hostitele a parazita; Host Specificity; parazitární nemoci u zvířat; cryptic species; Biodiversity; phylogeny; host specificity.; zvířata; Biological Evolution; Myxozoa; hostitelská specificita